2000
DOI: 10.1086/313583
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Multicenter Surveillance Study of Funguria in Hospitalized Patients

Abstract: Although fungal urinary tract infections are an increasing nosocomial problem, the significance of funguria is still not clear. This multicenter prospective surveillance study of 861 patients was undertaken to define the epidemiology, management, and outcomes of funguria. Diabetes mellitus was present in 39% of patients, urinary tract abnormalities in 37.7%, and malignancy in 22.2%; only 10.9% had no underlying illnesses. Concomitant nonfungal infections were present in 85%, 90% had received antimicrobial agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
182
3
21

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(219 citation statements)
references
References 16 publications
13
182
3
21
Order By: Relevance
“…Some investigators have showed that use of antibiotics, presence of central venous catheter, and prolonged hospital permanence represent important risk factors for the development of microorganisms (Kauffman et al 2000, Blumberg et al 2001, Simpson et al 2004). We verified in our work that all patients were under antibiotic use (100%).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have showed that use of antibiotics, presence of central venous catheter, and prolonged hospital permanence represent important risk factors for the development of microorganisms (Kauffman et al 2000, Blumberg et al 2001, Simpson et al 2004). We verified in our work that all patients were under antibiotic use (100%).…”
Section: Discussionmentioning
confidence: 99%
“…These three organisms were specifically chosen because they are major causes of bacteriuria and/or UTI in chronically catheterized persons. 14,15 …”
mentioning
confidence: 99%
“…No estudo de Kauffman e cols 17 , onde um total de 861 episódios de candidúria em pacientes hospitalizados foi avaliado, Candida albicans respondeu por 52% dos isolados, seguido por Candida glabrata e Candida tropicalis 16 (Tabela 2). 3 18 27 29 (Tabela 3).…”
Section: Condições Associadasunclassified
“…No estudo multicêntrico realizado por Kauffman e cols 17 onde mais de 800 pacientes foram avaliados, apenas 1% deles evoluíram com candidemia 17 . Em outra série de casos avaliada por Sobel e cols 36 , nenhum paciente com candidúria evoluiu para doença disseminada 36 .…”
Section: Dilemas Diagnósticos E Variáveis Determinantes Da Abordagem unclassified